The distribution of apolipoprotein E alleles in Scottish perinatal deaths - Becher, J‐C (BMJ Group, 2006)
BACKGROUND: The apolipoprotein E (ApoE) polymorphism has been well studied in the adult human population, in part because the e4 allele is a known risk factor for Alzheimer's disease. Little is known of the distribution of ApoE alleles in newborns, and their association with perinatal brain damage has not been investigated. METHODS: ApoE genotyping was undertaken in a Scottish cohort of perinatal deaths (n = 261), some of whom had prenatal brain damage. The distribution of ApoE alleles in perinatal deaths was compared with that in healthy liveborn infants and in adults in Scotland. RESULTS: ApoE e2 was over‐represented in 251 perinatal deaths (13% v 8% in healthy newborns, odds ratio (OR) = 1.63, 95% confidence interval (CI) 1.13 to 2.36 and 13% v 8% in adults, OR = 1.67, 95% CI 1.16 to 2.41), both in liveborn and stillborn perinatal deaths. In contrast, the prevalence of ApoE e4 was raised in healthy liveborn infants (19%) compared with stillbirths (13%, OR = 1.59, 95% CI 1.11 to 2.26) and with adults (15%, OR = 1.35, 95% CI 1.04 to 1.76). However, no correlation was found between ApoE genotype and the presence or absence of perinatal brain damage. CONCLUSIONS: This study shows a shift in ApoE allelic distribution in early life compared with adults. The raised prevalence of ApoE e2 associated with perinatal death suggests that this allele is detrimental to pregnancy outcome, whereas ApoE e4 may be less so. However, ApoE genotype did not appear to influence the vulnerability for perinatal hypoxic/ischaemic brain damage, in agreement with findings in adult brains and in animal models.